CLINICAL-PSYCHOLOGICAL REHABILITATION OF CARDIAC PATIENTS THROUGH OPTMIZATION OF THE SELF-PERCEPTION OF HEALTH - Nesterak, R.V.; Hasiuk, M.B. (World of Medicine and Biology, 2019)
Clinical-psychological rehabilitation with the author’s "Program of clinical and psychological rehabilitation of cardiologic patients by optimizing the self-perception of health " can be used to control the quality and effectiveness of rehabilitation of patients after acute coronary syndrome. It was established that the use of such an approach contributed to the change in objective and subjective data of patients, as well as to a healthy lifestyle. Along with this, the factors of improving the quality of rehabilitation are the use of complex medical therapy, close cooperation of a multidisciplinary team consisting of a cardiologist, a physician of physical and medical rehabilitation, a psychologist, a physical therapist and a patient.